Indoor Air Quality in Selected School Buildings in the Central Sector of Athens at the Attica’s Region and Potential Health Risks - Bikaki, Maria Anna; Dounias, Georgios; Farantos, Georgios; Cavoura, Olga; Damikouka, Ioanna; Evrenoglou, Lefkothea (European Scientific Journal, ESJ, 2025)
Aims and Scope: Indoor air pollution is a significant environmental risk factor for health, particularly in schools, where students and teachers spend a considerable portion of their day (about 30%). As a result, they are more exposed to indoor pollution than outdoor air pollution. This paper focuses on investigating the indoor air quality (IAQ) in school buildings within the Central Sector of Athens, in the Attica Region, by recording physical parameters and concentration levels of indoor air pollutants related to comfort, health, and safety conditions within classrooms. The study also seeks to identify factors contributing to diminished air quality in classrooms and propose measures to improve indoor air quality in school buildings to protect public health. Methods: The indoor air quality research was conducted in forty-seven (47) classrooms across twenty-six (26) school buildings in the Central Sector of Athens, in the Attica Region, from March 2022 to May 2023. Air pollutants, including Carbon dioxide (CO2), Carbon monoxide (CO), Volatile Organic Compounds (VOCs), Nitrogen dioxide (NO2), and Particulate matters (PM10, PM2.5), along with physical parameters such as temperature (T) and relative humidity (RH), were monitored using the series 500 Portable Air Quality Monitor (AeroQual) during one teaching hour per day in each classroom. Some windows and doors were opened during sampling due to health and safety measures and recommendations for COVID-19 protection for students and teachers. Findings: The overall mean concentrations of the main parameters recorded inside the schools were 0.136 ppm for CO, 823.38 ppm for CO2, 12.07 ppm for VOCs, 0.006 ppm for NO2, 38.1 μg/m3 for PM10, and 15.4 μg/m3 for PM2.5. The mean recorded temperature was 24.52 oC, and the relative humidity was 45.78%. In this study, twenty- two (22) classrooms, representing 46.8% of the schools in the Attica Region, were found to have temperatures outside the comfort range for students. In all cases, indoor CO concentrations were lower than the recommended exposure limit (REL) of 35 ppm, as an 8-hour time-weighted average (TWA) set by the National Institute of Occupational Safety and Health (NIOSH). Eight (8) of the forty-seven classrooms in the Attica region (17%) had CO2 concentrations exceeding 1000 ppm. VOCs exceeded the indoor limit value of 0.8 ppm in all schools (100%). There was a statistically significant difference between indoor and ambient air for CO, CO2, and ΝΟ2 (p<0.001), VOCs (p=0.004), and PM10 (p=0.028). Conclusion: The indoor air quality of the classrooms was influenced by outdoor air, the school’s location, the number of windows opened during lessons, the number of students in the classroom, the activities conducted, the furnishings, and the school equipment. Lack of comfort conditions and exceeded limits of indoor air pollutants can lead to diminished IAQ, thereby posing harmful effects on students. Proper ventilation of classrooms during lessons and breaks is necessary for better air quality. Ventilation is one of the most important factors affecting indoor air quality, as it dilutes exposure to agents originating indoors.